Aplicación de la ecografía ocular en todas sus modalidades: Revisión sistemática. - Brigitte de la Cruz, Sayonara; Villalba Espinal, Maria Nicole; Ordóñez Naranjo, Hernán Augusto; Fernandez Acosta, Ana Paula (Revista de Investigación en Salud VIVE)
Ocular ultrasound is a fundamental noninvasive assessment tool in ophthalmology, with multiple modalities (A-scan, B-scan, UBM, and Doppler ultrasound). This systematic review aims to evaluate the diagnostic and therapeutic utility, technical limitations, and multidisciplinary clinical applications of ocular ultrasound modalities (A-mode, B-mode, UBM, Doppler) by analyzing standardized operating protocols, correlating them with advanced imaging techniques, and their impact on clinical decision-making algorithms. Following the PRISMA methodology, research published between 2005 and 2025 in PubMed, Scopus, and Embase was examined. Original articles evaluating the diagnostic or therapeutic use of ocular ultrasound were included, excluding nonsystematic reviews and studies without quantifiable data. The Boolean operators AND OR were applied. Two independent reviewers performed the selection and extraction of information, with consensus to resolve discrepancies. Of 1,500 records identified, 34 met the inclusion criteria. The results indicate that: B-scan is the most commonly used modality (85% of studies) to evaluate retinal detachments and intraocular tumors. UBM provides high resolution in anterior pathologies (92% accuracy in narrow-angle glaucoma). Doppler ultrasound improves vascular diagnosis in central retinal vein occlusion (sensitivity of 89%). It is concluded that ocular ultrasound is essential in the diagnosis and monitoring of ocular diseases, with modalities adapted to various anatomical structures. Its integration with new technologies (AI, biomarkers) could optimize its clinical utility.